PENGARUH MARKETING ANALYTICS CAPABILITY TERHADAP SUSTAINED COMPETITIVE ADVANTAGE YANG DI MODERASI OLEH ADOPTION OF ARTIFICIAL INTELLIGENCE PADA PERUSAHAAN FARMASI DI PROVINSI JAWA TENGAH - Kaulika, Aya; Sabihaini (Jurnal Manajemen Indonesia, 2025)
This study aims to analyze the influence of marketing analytics capability on sustained competitive advantage in pharmaceutical companies in Central Java Province, as well as examine the role of market sensing, market seizing, and market reconfiguring mediation. In addition, this study also examines the role of moderation adoption of artificial intelligence in strengthening the relationship between variables. The methodology used was data collection through questionnaires from 55 pharmaceutical companies and analysis using the Partial Least Square method. The results of the study show that marketing analytics capability has a significant effect on sustained competitive advantage, both directly and through the mediation of dynamic capabilities consisting of market sensing, market seizing, and market reconfiguration. In addition, the adoption of artificial intelligence has been proven to strengthen the relationship between marketing analytics capabilities and dynamic capabilities. These findings underscore the importance of strengthening data-driven analytics capabilities and leveraging artificial intelligence technology to maintain a sustainable competitive advantage. This research makes an original contribution in expanding the understanding of the integration of marketing analytics and artificial intelligence in the context of dynamic capabilities in the pharmaceutical industry. The practical implications of this research are the need for companies to invest in analytics and artificial intelligence technologies to improve market responsiveness and adaptability in the face of changing business environments.